Analisis Pemilihan Moda Transportasi Penumpang Antara Kereta Api dan Bus Rute Bandar Lampung – Palembang dengan Metode Discrete Choice Model - Sentanu, Wayan Yogie; Purba, Aleksander; Sulistyorini, Rahayu (Universitas Lampung, 2021)
Choosing the right mode of transportation is something that passengers want, but with the advantages and disadvantages of existing transportation modes can affect the number of users of these modes of transportation. The purpose of this study was to determine the factors and probability of choosing the mode of passenger transportation between trains and buses with the Bandar Lampung - Palembang route. The method used in this research is the Discrete Choice Model method, with the analysis used is linear regression analysis of the two models used, namely the difference binary logit model and the binary logit ratio. Based on the research results, the probability value from the bus mode selection analysis is known if the value (∆C) = 0, the probability value with the binary logit model is the difference = 35%, and if the value (∆C) = 100000 then the probability value increases to 41%. Meanwhile, if (C1 / C2) = 0.1, then the probability value with the binary logit model ratio = 58%, and if the value (C1 / C2) = 1 then the probability value increases to 35%. From the results of the analysis carried out, the dominant factors influence the choice of mode of transportation by route Bandar Lampung - Palembang is the cost of transportation cheap, and comfort level of service.Keywords : modal choice, binary logit, discrete choice model, probability